(untitled) - Sidonia Dalby (New York, 1996)
The book includes how to obtain a U.S. student visa; how to choose a U.S. college; how U.S. colleges make admissions decisions; and how to handle applications and interviews
Keywords: universities and colleges - united states - admission - handbooks, manuals, etc